Effect of carbon nanotube loading on electrical properties of electrospun polyvinylidene fluoride (PVDF) fiber - Jia, Wei Lee; Syed Bakar, Sharifah Shahnaz; Ahmad Zaidi, Nur Hidayah; Yahud, Shuhaida; Samat, Noorasikin (IOP Publishing Ltd, 2021)
Polyvinylidene fluoride (PVDF) is a high purity thermoplastic fluropolymer that use in the aircraft, electronics, and chemical industry. Carbon nanotube (CNTs) is made up of rolled up of graphite sheets, exhibits excellent chemical, thermal, mechanical properties, and large surface areas. PVDF fibers blended with CNTs were able to enhance the β-phase which contributes to piezoelectric properties. Electrospinning is the simplest and low-cost method to produce PVDF/CNT fibers by dissolving PVDF in solvent N, N-Dimethylformamide (DMF). 15wt% PVDF solution was used. CNT loading were varied at 0.0wt%, 0.35wt%, 0.80wt% and 1.00wt% with parameters of 20kV, tip-to-collector distance (TCD) 15cm and flow rate 1.0mLh-1. Scanning Electron Microscope (SEM), four-point probe and X-ray Diffraction (XRD) were used to determine the morphology and crystallinity of electrospun PVDF/CNT fibers. The SEM analysis concluded all fibers showed beaded structure due to low concentration of PVDF solution with insufficient ultrasonification and stirring, cause electrospraying and agglomeration. XRD and four-point probe analysis concluded PVDF/0.35wt%CNT showed the highest β-phase content with intense XRD peak and highest electrical conductivity. However, shift peak is observed among all fibres due to short electrospinning time leads to insufficient thickness of electrospun mat, which affects the mechanical properties of fibres and causes peak shift.